The effects of dronabinol during detoxification and the initiation of treatment with extended release naltrexone. (1st September 2015) - Bisaga, Adam; Sullivan, Maria A.; Glass, Andrew; Mishlen, Kaitlyn; Pavlicova, Martina; Haney, Margaret; Raby, Wilfrid N.; Levin, Frances R.; Carpenter, Kenneth M.; Mariani, John J.; Nunes, Edward V.
Highlights: We examined effects of THC in opioid dependent individuals treated with naltrexone. Oral THC decreased the severity of opioid withdrawal severity at treatment outset. Oral THC did not improve retention in treatment with injectable naltrexone. Naturalistic marijuana smoking was associated with improved retention in treatment. Abstract: Background: Evidence suggests that the cannabinoid system is involved in the maintenance of opioid dependence. We examined whether dronabinol, a cannabinoid receptor type 1 partial agonist, reduces opioid withdrawal and increases retention in treatment with extended release naltrexone (XR-naltrexone). Methods: Opioid dependent participants were randomized to receive dronabinol 30 mg/d ( n  = 40) or placebo ( n  = 20), under double-blind conditions, while they underwent inpatient detoxification and naltrexone induction. Before discharge all participants received an injection of XR-naltrexone, with an additional dose given four weeks later. Dronabinol or placebo was given while inpatient and for 5 weeks afterwards. The primary outcomes were the severity of opioid withdrawal, measured with the Subjective Opioid Withdrawal Scale, and retention in treatment at the end of the inpatient phase and at the end of the 8-week trial. Results: The severity of opioid withdrawal during inpatient phase was lower in the dronabinol group relative to placebo group ( p  = 0.006). Rates of successful induction onto XR-naltrexone (dronabinol 66%, placebo 55%) and completion of treatment (dronabinol 35%, placebo 35%) were not significantly different. Post hoc analysis showed that the 32% of participants who smoked marijuana regularly during the outpatient phase had significantly lower ratings of insomnia and anxiety and were more likely to complete the 8-week trial. Conclusion: Dronabinol reduced the severity of opiate withdrawal during acute detoxification but had no effect on rates of XR-naltrexone treatment induction and retention. Participants who elected to smoke marijuana during the trial were more likely to complete treatment regardless of treatment group assignment.